2021
DOI: 10.1002/hbe2.268
|View full text |Cite
|
Sign up to set email alerts
|

Zooming through development: Using video chat to support family connections

Abstract: Video chat may allow young children and grandparents to develop and maintain bonds when they are physically separated because it enables them to share experiences with each other in real time. We used an ecological model framework to examine factors associated with the development of the grandparent-grandchild relationship during the COVID-19 pandemic, when many families were experiencing reduced opportunities for in-person interaction. We analyzed survey data from grandparents (N = 855) and parents (N = 846) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 67 publications
0
38
0
1
Order By: Relevance
“…In contrast, when connectivity was available, children experienced benefits not only for ongoing education, but also evidenced by the ability to stay connected to remote family members, particularly grandparents (Strouse et al, 2021). The COVID-19 pandemic significantly disrupted in-person relationships with grandparents, extended family, caregivers, educators, and peers.…”
Section: Media Use and The Covid-19 Pandemic—a Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, when connectivity was available, children experienced benefits not only for ongoing education, but also evidenced by the ability to stay connected to remote family members, particularly grandparents (Strouse et al, 2021). The COVID-19 pandemic significantly disrupted in-person relationships with grandparents, extended family, caregivers, educators, and peers.…”
Section: Media Use and The Covid-19 Pandemic—a Case Studymentioning
confidence: 99%
“…Prior research demonstrated that video chats can help families maintain existing relationships with grandparents (McClure & Barr, 2017). Frequency of video chat between June and August 2020 was the best predictor of grandparent's ratings of closeness to their grandchild, after controlling for how far apart they lived from one another (Strouse et al, 2021). These findings suggest that access to stable high-speed Internet benefited family well-being by maintaining multigenerational links with frequent video chat contact during the pandemic.…”
Section: Media Use and The Covid-19 Pandemic—a Case Studymentioning
confidence: 99%
“…The second theme that emerges from this collection of papers is that despite high levels of exposure to and familiarity with screen media-nearly all families with children under 8 years have a mobile device (98%), TV (97%), or computers (88%) in the home (Rideout & Robb, 2020) (Pila et al, 2021). In addition, families are coming to appreciate certain technologies, such as video chat, as a means of creating and supporting relationships between adults and young children, especially when circumstances, such as the COVID-19 pandemic, limit inperson interactions (Strouse et al, 2021). Because families often serve as gatekeepers for the types of technologies children use and how they interact with them, family-level variables may also influence children's understanding of emerging technologies.…”
Section: Emerging Themesmentioning
confidence: 99%
“…For children, the loss of contextual knowledge that in-person contact allows is particularly important, and this is a major limitation in the usefulness of digital contact between children and their families ( Iyer, Albakri et al, 2020 ). For video calling to allow very young children to maintain connections with family members, adults need to scaffold interactions ( Strouse et al, 2021 ). This involves knowing how to use the technology and set up the calls, as well as supporting children to stay engaged when they get bored, walk off screen, or struggle with the conversation ( Ames et al, 2010 ; Iyer, Albakri et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%